2016
DOI: 10.1139/cjss-2016-0019
|View full text |Cite
|
Sign up to set email alerts
|

Precision and Accuracy of Time Domain Reflectometry and Capacitive Probes to Determine Soil Electrical Conductivity in Cranberry Production – Technical Note

Abstract: A recent study suggests a sensitivity of cranberry to saline stress. Consequently, monitoring of soil electrical conductivity may help growers to identify areas where plants could be under stress due to salt deposits. We used two different types of probes, a time-domain reflectometry (TDR; model CS645 probe) and a capacitive approach (model GS3 probe) to estimate electrical conductivity (EC) or conductance (G). The estimates were compared with measurements of EC in soil pore water using suction lysimeters in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 21 publications
0
8
2
Order By: Relevance
“…The decline in photosynthesis and differences in EC were greater when the treatments were drier (i.e., under lower SWP conditions). The study also showed that EC could be reliably monitored with a capacitive probe with no calibration, or with a calibrated time-domain reflectometry probe (Samson et al 2017a). In absence of calibration of the capacitive probe though, the study showed that a 0.21 dS m −1 error is observed, and then, calibration would bring additional accuracy if needed.…”
Section: Water Table Controlmentioning
confidence: 95%
See 1 more Smart Citation
“…The decline in photosynthesis and differences in EC were greater when the treatments were drier (i.e., under lower SWP conditions). The study also showed that EC could be reliably monitored with a capacitive probe with no calibration, or with a calibrated time-domain reflectometry probe (Samson et al 2017a). In absence of calibration of the capacitive probe though, the study showed that a 0.21 dS m −1 error is observed, and then, calibration would bring additional accuracy if needed.…”
Section: Water Table Controlmentioning
confidence: 95%
“…Because cranberry roots grow close to the soil surface, salt accumulation may be detrimental to berry crops (Samson et al 2017a(Samson et al , 2017b. A paucity of information exists on the tolerance of cranberry to ion accumulation in the root zone under field conditions.…”
Section: Water Table Controlmentioning
confidence: 99%
“…The first commercial devices that were used to measure σ b were based on the measurement of the soil electrical resistance (ER) by means of four-electrode integrated probes [19]. Nowadays, the ER technique is still arguably the most widely used for σ b measurement, mostly because it is used in the simplified two-electrode sensors that are integrated within the capacitance-conductance combined (CCC) probes [20][21][22]. Other sensors for σ b measurement are based on reflectometry, remarkably in the time domain (TDR) [12,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The rapid information obtained with these proximal probes can be readily used in a sustainable agriculture framework for monitoring and, eventually, for decision-making. Empirical or semi-empirical calibrations have been almost always used to estimate σ e from σ b , and since the σ b values obtained with the different available sensors are also different, not only site-specific, but also sensor-proprietary calibrations have been developed [20][21][22]. The calibrations have been developed mostly under laboratory conditions using sandy soils [22,33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, showed that water table management can meet 30% of the daily ET demand. However, Samson et al (2017aSamson et al ( , 2017b cautioned that subirrigation may induce plant stress due to increased soil salinity.…”
mentioning
confidence: 99%